2018
DOI: 10.2807/1560-7917.es.2018.23.47.1700837
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus surveillance: first dengue virus detection in local Aedes albopictus mosquitoes in Europe, Catalonia, Spain, 2015

Abstract: Dengue has emerged as the most important viral mosquito-borne disease globally. The current risk of dengue outbreaks in Europe appeared with the introduction of the vector Aedes albopictus mosquito in Mediterranean countries. Considering the increasing frequency of dengue epidemics worldwide and the movement of viraemic hosts, it is expected that new autochthonous cases will occur in the future in Europe. Arbovirus surveillance started in Catalonia in 2015 to monitor imported cases and detect possible local ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Our ndings showed concurrent co-circulation of similar serotypes and genotypes in mosquitoes and patients, which is similar to the results of a previous study that detected the DENV in both Aedes albopictus mosquitoes and viraemic patient in Catalonia, Spain [38]. Sequencing and phylogenetic analyses showed that the detected DENVs grouped primarily into three genotypes, namely: (1) DENV-1 genotype IV, (2) DENV-2 Cosmopolitan genotype, and (3) DENV-4 genotype II, suggesting the hyperendemicity of dengue in Tarlac City, Philippines.…”
Section: Discussionsupporting
confidence: 91%
“…Our ndings showed concurrent co-circulation of similar serotypes and genotypes in mosquitoes and patients, which is similar to the results of a previous study that detected the DENV in both Aedes albopictus mosquitoes and viraemic patient in Catalonia, Spain [38]. Sequencing and phylogenetic analyses showed that the detected DENVs grouped primarily into three genotypes, namely: (1) DENV-1 genotype IV, (2) DENV-2 Cosmopolitan genotype, and (3) DENV-4 genotype II, suggesting the hyperendemicity of dengue in Tarlac City, Philippines.…”
Section: Discussionsupporting
confidence: 91%
“…This is the case of the invasive Asian tiger mosquito Aedes albopictus, which is associated with the local transmission of pathogens such as filarioid worms (e.g., Dirofilaria spp. ), protozoa (e.g., avian malaria parasites), and viruses (e.g., Dengue virus) (4)(5)(6). This species has a broad global distribution and is present in countries outside its native range in America, Europe, Oceania, and Africa (7).…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Europe autochthonous DENV transmission episodes have occurred on several occasions (29), with a recent detection of Ae. albopictus mosquitoes infected with DENV in Spain in 2015 (the rst detection in Europe) (30). Arbovirus surveillance is extremely important to identify possible foci of transmission, and this relies on multidisciplinary activities, including community engagement to early detect the mosquito and control its population, especially in urban areas (30).…”
Section: Discussionmentioning
confidence: 99%